Metabolite Activity of Endophy Fungi Isolated from Betle Leaf (Piper betle) Against Candida Albicans - Aini Aini; Edi Kurniawan; Sumiatun Sumiatun (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Betle (Piper betle) is a type of plant producing antimicrobial substances and secondary metabolites that are potentially used for the production of new drugs. Candidiasis is a disease caused by Candida albicans and causes diseases of the mucosa of the mouth, digestive tract, and vagina. The study aimed to isolate the betle leaf endophyte fungus (Piper betle L.) and find out the activity of its metabolites against Candida albicans. The research was conducted at the Laboratory of Plant Physiology and Biotechnology, Faculty of Agriculture, University of Mataram. The research method used was descriptive observation. The purpose of this study was to isolate endophytic fungi and their activity against Candida albicans from beetle leaves. The yield of endophytic fungal secondary metabolites was obtained by fermentation method, and the activity of Candida albicans was detected by diffusion method. Isolation test obtained from R&D hospital NTB Province. The research results obtained the endophytic fungi isolated from beetle leaves (Piper betle L.) and obtained the identification results of the fungus Cephalosporium.